Cybernetics and Mathematics Applications in Intelligent Systems Proceedings of the 6th Computer Science On-line Conference 2017 (CSOC2017), Vol 2 - Silhavy, Radek; Senkerik, Roman; Kominkova Oplatkova, Zuzana; Prokopova, Zdenka; Silhavy, Petr.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents new methods for and approaches to real-world problems as well as exploratory research describing novel mathematics and cybernetics applications in intelligent systems. It focuses on modern trends in selected fields of technological systems and automation control theory. It also introduces new algorithms, methods and applications of intelligent systems in automation, technological and industrial applications.  This book constitutes the refereed proceedings of the Cybernetics and Mathematics Applications in Intelligent Systems Section of the 6th Computer Science On-line Conference 2017 (CSOC 2017), held in April 2017.
Cost-Effective Computational Modelling of Fault Tolerant Optimization of FinFET-based SRAM Cells --  Application of Risk Theory Approach to Fuzzy Abduction --  Enhanced TDS Stability Analysis Method via Characteristic Quasipolynomial Polynomization.- Dissipativity of Multistep Runge-Kutta Methods for Nonlinear Neutral Delay Integro Differential Equations with Constrained Grid --  Maze Navigation in the Ball & Plate Model -- Large Networks of Diameter Two Based on Cayley Graphs.- Analysis of the IoT WiFi mesh network.- Lightning Impulse Voltage Evaluation.- Big Data Process Advancement.- LDPC Binary Vectors Coding Enhances Transmissions and Memories Reliability.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence